2016
DOI: 10.1017/s1092852916000523
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine compared to placebo and other agents with antidepressant activity in patients with unipolar and bipolar depression: a comprehensive meta-analysis of efficacy and safety outcomes in short-term trials

Abstract: Lamotrigine was superior to placebo in improving unipolar and bipolar depressive symptoms, without causing more frequent adverse effects/discontinuations. Lamotrigine did not differ from lithium, olanzapine+fluoxetine, citalopram, or inositol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 76 publications
0
35
0
2
Order By: Relevance
“… 28) However, researchers indicated the methodological flaws in double blind trials reporting negative results, 29) and the superiority of LMT over placebo was reported in a meta-analysis as a monotherapy and augmentation strategy. 30) Moreover, recent evidence-based guidelines recommend the use of LMT in patients with bipolar depression. 24 , 31 , 32) …”
Section: Discussionmentioning
confidence: 99%
“… 28) However, researchers indicated the methodological flaws in double blind trials reporting negative results, 29) and the superiority of LMT over placebo was reported in a meta-analysis as a monotherapy and augmentation strategy. 30) Moreover, recent evidence-based guidelines recommend the use of LMT in patients with bipolar depression. 24 , 31 , 32) …”
Section: Discussionmentioning
confidence: 99%
“…For divalproex monotherapy, 4 small trials suggest possible value in acute bipolar depression (Table 4), but it remains FDA-unapproved for depression or long-term treatment in BD. Evidence that lamotrigine is effective in acute bipolar depression rests on pooling inconsistent data, including from individually failed trials vs. placebo (Table 4) (Solmi et al 2016). Lamotrigine is FDA-approved only for long-term prophylaxis in BD, with partial effectiveness against recurrences of depression but little efficacy against acute or recurrent mania (Frye et al 2011;Baldessarini 2013).…”
Section: Mood-stabilizersmentioning
confidence: 99%
“…A comprehensive meta-analysis of efficacy and safety outcomes in short-term trials of lamotrigine compared to placebo and other agents with antidepressant activity in patients with unipolar and bipolar depression showed that lamotrigine did not differ regarding efficacy on depressive symptoms, response, or remission from lithium (Solmi et al 2016). …”
Section: Lithium Augmentation In Acute Treatment Of Depressionmentioning
confidence: 99%